Public politicians electoral potential in social media - N. A. Yushkina (Вестник университета, 2022)
The object of the study are representatives of Russian political elite and their electorate in social networks. The aim of the study is to assess the impact on the electoral potential of politicians of their online communications with their audiences. The main quantitative indicators of the presence and activity of the Russian public politicians on Facebook, Instagram and Youtube, successful interaction forms between government representatives and the society, indexes of popularity, activity, audience loyalty, as well as visual features of the accounts’ content were analysed. Feedback in the accounts of current politicians was assessed, including containing critical discourse. According to the results of the study, the author concluded that the creation of a full-fledged feedback channel with a potential electorate positively affects the image of a public politician, allows reducing the feedback amount with negative comments, is a successful interaction form between a politician and the electorate and increases his electoral potential. However, the Russian politicians are not sufficiently prepared to establish communication with the potential electorate via social media.